BLOOD GLUCOSE LEVEL AND ORGANOLEPTIC EVALUATION OF THE NATIVE AND UPGRADED NATIVE CHICKEN - Bejar, Feleciano R.; Baylon, Manuel J.; Paldez, Romeo N.; Bejar, Elvie T.; R. Aquino, Reynaldo (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The study focused on the evaluation of the Blood glucose and organoleptic attributes of the progeny of Kabir and native chicken as well as progeny of native and native chicken. The parameters included in this study were; live and carcass weight, dressing percentage, giblets weight, weights of meat cuts, skin and flesh color acceptability, desirability, intensity, texture, tenderness, juiciness, general acceptability. Results showed that live and dressed weights between the two F1 crosses both fasted and non-fasted showed significantly different, with kabir-native cross showed higher or heavier weights. The result has an economic bearing the fact that fasting before dressing the chicken can be practiced without compromising the dressing percentage. The results on meat cuts, data showed significantly higher for kabir-native F1 cross, except for the weights of heart, wings, head and neck, and feet which showed no significant difference between the two F1 crosses. Data on skin color did not vary significantly between the two groups of progenies. Flesh color of the meat between the two groups differ significantly with native-native cross significantly higher than the kabir-native cross. Acceptability of the carcass color is significantly higher for the kabir-native F1 considering its color combination of pale pink with yellow tinge color which probably contributed attraction to the meat The general acceptability results for the two groups of meat ranges from 3.23±0.92 to 3.85±1.15. The Native-native F1 meat samples had significantly higher than the kabir-native F1 meat samples. The relatively higher sensory scores for native-native F1 meat except on intensity and tenderness could have contributed to the overall appraisal of the meat.